Detection of salmonella bacterium in drinking water using microring resonator - Mahdi, Bahadoran; Ahmad Noorden, Ahmad Fakhrurrazi; Mohajer, Faeze Sadat; Abd Mubin, Mohamad Helm; Chaudhary, Kashif; Jalil, Muhammad Arif; Ali, Jalil; Yupapin, Preecha (Taylor and Francis Ltd., 2016)
A new microring resonator system is proposed for the detection of the Salmonella bacteriumin drinking water, which is made up of SiO 2 -TiO 2 waveguide embedded inside thin film layer of the flagellin. The change in refractive index due to the binding of the Salmonella bacteriumwith flagellin layer causes a shift in the output signal wavelength and the variation in through and drop port’s intensities, which leads to the detection of Salmonella bacteriumin drinking water. The sensitivity of proposed sensor for detecting of Salmonella bacterium in water solution is 149 nm/RIUand the limit of detection is 7  10  4 RIU.